The Effect of Work Engagement and Motivation on Employee Performance with Employee Competence as A Mediation Variable in The Directorate General of Empowerment of the Ministry of Protection of Indonesian Migrant Workers (KP2MI) - Triani, Junita; Suharto, Suharto; Mei R, Dhistianti (Dinasti International Journal of Management Science, 2025)
This study aims to determine and analyze the effect of 1). work engagement on employee performance, 2). motivation on employee performance, 3). competence on employee performance, 4). work engagement on competence, 5). motivation on competence, 6). work engagement on employee performance through competence, 7). Motivation for employee performance through competence. The study was conducted by the Directorate General of Empowerment of the Ministry of P2MI with a research sample of 60 respondents. The sampling technique used was a saturated technique. The data analysis method used descriptive analysis and path analysis. The results of the study indicate that 1). There is an influence of work engagement on employee performance 2. There is an influence of motivation on employee performance 3. There is an influence of competence on employee performance, 4). There is an influence of work engagement on competence, 5). There is an influence of motivation on competence, 6). There is an influence of work engagement on employee performance through competence, 7). There is an influence of motivation on employee performance through competence.